Desain Sistem Informasi Puskesmas Perawatan di Dinas Kesehatan Kota Semarang Menggunakan RAD - Yudit Saputri, Adinda Choirunnisa (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2026)
A care health center is a first-level health facility that has the responsibility of recording and monitoring service data to support the measurement of hospitalization indicators by the Health Office. The recording process that is still carried out semi-manually poses weaknesses in terms of effectiveness, accuracy, and speed of reporting. This research aims to develop a web-based information system to facilitate the recording and monitoring of inpatient service data at the Semarang City Treatment Health Center. The Rapid Application Development (RAD) method is used as an iterative development approach by involving users at each stage. The system built provides features for recording data on emergency patients, inpatients, number of beds, health workers, and days of treatment. The recorded data is processed into service indicators, namely Bed Occupancy Rate (BOR), Length of Stay (LOS), and Turn Over Interval (TOI), which are presented in the form of interactive charts on the dashboard page. In addition, the system is equipped with role-based user management. The results of the implementation show that the system is able to improve accuracy, speed up reporting, and support more efficient and data-based evaluation of service performance. Testing using the Blackbox method as well as direct observation confirmed that the system was easy to use, responsive, and met the needs of users.